Accuracy of the CoaguChek XS for point-of-care international normalized ratio (INR) measurement in children requiring warfarin - Bauman, Mary E.; Black, Karina L.; Massicotte, Mary P.; Bauman, Michelle L.; Kuhle, Stefan; Howlett-Clyne, Susan; Cembrowski, George S.; Bajzar, Laszlo (Thrombosis and Haemostasis, 2008)
Point-of-care INR (POC INR) meters can provide a safe and effective method for monitoring oral vitamin K antagonists (VKAs) in children. Stollery Children’s Hospital has a large POC INR meter loan program for children requiring oral VKAs. Our protocol requires that POC INR results be compared to the standard laboratory INR for each child on several consecutive tests to ensure accuracy of CoaguChek XS® (Roche Diagnostics, Basel Switzerland) meter. It was the objective of the study to determine the accuracy of the CoaguChek XS by comparing whole blood INR results from the CoaguChek XS to plasma INR results from the standard laboratory in children. POC INR meter validations were performed on plasma samples from two time points from 62 children receiving warfarin by drawing a venous blood sample for laboratory prothrombin (PT)-INR measurements and simultaneous INR determinations using the POC-INR meter. Agreement between CoaguChek XS INR and laboratory INR was assessed using Bland-Altman plots. Bland-Altman's 95% limits of agreement were 0.11 (-0.20; 0.42) and 0.13 (-0.22; 0.48) at the two time points, respectively. In conclusion, the CoaguChek XS meter appraisal generates an accurate and precise INR measure in children when compared to laboratory INR test results.
Keywords: Point-of-care; international normalized ratio; warfarin; home monitoring; child